PROFILE OF ANIMATION INTERACTIVE MEDIA ON BIOGEOCHEMICAL CYCLE MATTER FOR SENIOR HIGH SCHOOL - MA'DAN HAIKAL ADHIM (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
Animation interactive media can explain an abstract concept to more real. This research aimed to produce biogeochemical cycle animation interactive media which is fesiable theoretically. Feasibility theoretically got from a results of media validity by biology lecturers and teachers. The validation media aspects are graph quality, animation quality, program quality, physical quality, present quality, matter quality, and illustration quality. This development research used ASSURE model which consist of six phases. The validation media result percentage was 85,26% and got very feasible category that implementation feasible in the learning. Keywords: animation interactive media, biogeochemical cycle, feasibility theoretically